The Siphonal mantle of Tridacna crèche - Naguit, Maria Rio A. (Silliman Journal, 2008)
Tridacna crocea is the smallest among the eight species of Family Tridacnidae and the most abundant tridacnids in reefs around the Philippine archipelago. This investigation describes the characteristic mantle pattern and color of T. crocea and correlates them to genetic structure; verifies the characteristic mantle color and pattern of T. crèche underwater and differentiates it from its closely related species, T. maxima in the field. Tissue samples of Tridacna crocea and T. maxima were collected and preserved in 95% alcohol. Prior to any mantle collection, each clam was photographed. Thirteen mantle patterns were identified from the 174 Tridacna crocea individuals of six reef areas: Pemican, Tanon Strait, Carbin, Camiguin, Southeastern Samar and Spratlys. Results revealed that Tridacna crocea can be distinguished from T. maxima in the field by the appearance and arrangement of their hyaline organs. Moreover, analysis on genotype-phenotype correlation using the T. crocea mantle morphology/colour, found no significant relationship between the mantle morphs and genetic structure of the individuals.